Influence of Anemia on Postoperative Cognitive Function in Patients Undergo Hysteromyoma Surgery - You, Zhijian; Chen, Lesi; Xu, Hongxia; Huang, Yidan; Wu, Jinglei; Wu, Jiaxuan (Frontiers in Molecular Biosciences, 2021)
Cognitive dysfunction is a common disease in aging population. This study aims to compare the influence of different degrees of anemia on the cognitive function of patients undergo hysteromyoma surgery. Sixty-one patients aged 18-60 years who underwent uterine fibroid surgery in the Second Affiliated Hospital of Shantou University Medical College from March 2019 to December 2020 were selected for this study. Patients were divided into three groups: group normal (Group N, patients have no anemia), group of mild anemia (Group Mi, patients have mild anemia) and group of moderate anemia (Group Mo, patients had moderate anemia). Combined spinal and epidural anesthesia were administered. Cognitive function tests were performed one day before the surgery and repeated at the 5th and 30th days after surgery. Peripheral venous blood samples from patients were collected before the surgery, right after surgery and at the 24th and 72nd hours after surgery. The contents of S-100β, IL-6, TNF-α and IL-1β in serum samples were determined by ELISA. It was found that there were no significant differences in general characteristics of patients among Group N, Group Mi and Group Mo(P > 0.05). Nine patients developed postoperative cognitive dysfunction after surgery, and the incidence was 14.75% (9/61). The incidence of postoperative cognitive dysfunction (POCD) was 40% in Group Mo, which was higher than that in Group N and Group Mi. The difference was statistically significant(P<0.05). Inflammatory factors in patients with POCD were higher in post-surgery than before-surgery (P<0.05), while there was no statistical significance in the difference of inflammatory factors of patients without POCD before and after surgery (P>0.05). Taken together, this study suggested that moderate anemia could be a risk factor of POCD in patients undergoing hysteromyoma surgeries. This study will help surgeons developing measures for preventing the occurrence of POCD.